2011
DOI: 10.1007/s00436-011-2769-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel long-lasting impregnation technique transferred from clothing to bednets: extended efficacy and residual activity of different pyrethroids against Aedes aegypti as shown by EN ISO 6330-standardized machine laundering

Abstract: A novel long-lasting insecticide-treated net (LLIN) has been designed by embedding the pyrethroids deltamethrin, cyfluthrin, permethrin, or etofenprox, onto the fibres of bed net cotton fabric by transferring a new polymer-coating technique from clothing to netting material. EN ISO 6330, the more stringent European Norm for domestic washing and drying procedures for textile testing, has been newly employed to monitor and validate more precise wash durability and residual bioactivity of LLINs. Wash durability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The ISO 6330∶2000 machine washing procedure that is considered to be the more stringent [27] (European standard for domestic washing procedure for textiles testing), seems to have less impact compared to the laboratory washing procedure which is considered as a hand simulation washing procedure [41]. So applying the ISO 6330∶2000 machine washing with the IEC A* detergent to the nets underestimates the loss of active ingredient due to washes.…”
Section: Resultsmentioning
confidence: 99%
“…The ISO 6330∶2000 machine washing procedure that is considered to be the more stringent [27] (European standard for domestic washing procedure for textiles testing), seems to have less impact compared to the laboratory washing procedure which is considered as a hand simulation washing procedure [41]. So applying the ISO 6330∶2000 machine washing with the IEC A* detergent to the nets underestimates the loss of active ingredient due to washes.…”
Section: Resultsmentioning
confidence: 99%
“…Permethrin or etofenprox did not enhance the spatial repellency as well as landing, probing and/or biting protection efficacy of DEET and IR3535 in combined LLIRNs when compared with the equivalent concentrations on the corresponding LLRNs. Accordingly, it could recently be demonstrated that pyrethroids like deltamethrin, cyfluthrin, permethrin and etofenprox impregnated onto LLINs do not prevent from landing, probing and biting activity of A. aegypti when using the arm-in-cage test (Faulde et al 2012). However, even low concentrations of DEET or IR3535 directly influence mosquito landing and probing frequency, hot-feet effect, excito-repellency and spatial repellency in LLIRNs.…”
Section: Discussionmentioning
confidence: 98%
“…Quantification of permethrin, etofenprox, DEET and IR3535 Measurement of permethrin, etofenprox, DEET and IR3535 in unwashed fabrics was accomplished by using the validated method of the Central Institute of the German Armed Forces Medical Service Koblenz (Faulde et al , 2012. In order to receive a representative sample of the given material, at least five subsamples were removed from different locations (depending on the available amount of the material) and cut into pieces of approximately 0.5 square centimetres.…”
Section: Methodsmentioning
confidence: 99%
“…Lack of protection against landing and biting mosquitoes when LLIN contacts the skin is known; a complete lack of biting protection of deltamethrin and permethrin LLINs was reported by Faulde et al . [33] against Aedes aegypti . This inability of LLINs in contact with the body to prevent landing and biting mosquitoes suggests low levels of spatial repellence from permethrin.…”
Section: Discussionmentioning
confidence: 99%